Detachment and recovery of an X-ray opaque tip of a disposable guide sheath kit: A rare complication of endobronchial ultrasound-guided transbronchial biopsy - Naoya Yasokawa; Noboru Yorizumi; Koji Kurose; Masaaki Abe; Toru Oga (Respiratory Medicine Case Reports, 2020)
Endobronchial ultrasound with a guide sheath (EBUS-GS)-guided transbronchial biopsy offers advantages and is frequently used for the diagnosis of peripheral pulmonary lesions. A previously healthy 75-year-old man was hospitalized to undergo bronchoscopy for the diagnosis of a mass with a diameter of about 40 mm in right S3 area. The mass was detected during a regular medical check-up, and lung cancer was suspected. EBUS-GS guided transbronchial biopsy was performed through the right B3. Following the bronchoscopic procedure and removal of the GS, we observed that an X-ray opaque tip attached to the point of the GS was missing. We examined the lung field through X-ray fluoroscopy and found that the detached opaque tip was located in the right middle lung field. We re-inserted the bronchoscope, and successfully recovered it using transbronchial biopsy forceps. The rate of complications in EBUS-GS is low, and the complication presented in this report is rare. Physicians should exercise caution when performing this procedure and carefully check the condition of the kit to reduce the risk of such complications. Keywords: Endobronchial ultrasound with a guide sheath (EBUS-GS), X-ray opaque tip, Peripheral pulmonary lesions